Handbook of research on the role of libraries, archives, and museums in achieving civic engagement and social justice in smart cities - Taher, Mohamed, 1955- (Advances in library and information science (ALIS) book series., 2022)
"This book examines the application of tools and techniques in Libraries, Archives and Museums (LAM)'s literacy with an aim to improve skills and competency in achieving civic engagement and social justice and promoting social inclusion and civic participation"--